2009
DOI: 10.1063/1.3168493
|View full text |Cite
|
Sign up to set email alerts
|

A planar-type surface-wave plasma source with a subwavelength diffraction grating inclusion for large-area plasma applications

Abstract: The electromagnetic wave through the subwavelength diffraction grating can be largely absorbed by surface-wave plasmas (SWPs). A SWP source is built with two slot-array antennas element. Due to the dissipation of surface waves in overdense plasmas, this source can provide remarkable discharge efficiency of 4.4 cm2/W experimentally and 96% of incident power numerically. When the applied power as low as 200 W is supplied to the SWP source, a homogeneous plasma with the uniform area up to 14×36 cm2 and the plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 20 publications
0
20
0
1
Order By: Relevance
“…IV. Figure 1 show the schematic of the plasma source, which has been reported in our previous works, [16][17][18][19] but its energy coupling parts in the present setup will be reset for studying the influences of different wave-mode conversion devices on plasma heating. The cavity dimensions are x =0-46 cm, y =0-22 cm, and z =0-30 cm.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…IV. Figure 1 show the schematic of the plasma source, which has been reported in our previous works, [16][17][18][19] but its energy coupling parts in the present setup will be reset for studying the influences of different wave-mode conversion devices on plasma heating. The cavity dimensions are x =0-46 cm, y =0-22 cm, and z =0-30 cm.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, the development and application researches of the large-scale overdense SWP have attracted the unprecedented attention and the current study focus on the spatial uniformity and the temporal stability in large area. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] To address the above concerns, a lot of planar-type SWP sources have been optimized. As for these sources, the uniformity of plasma below the dielectric slab is one of the most important factors.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Characterized by non-uniformity of plasma distributions, a high number density of neutral particles, a broad frequency range of electron-neutral collisions, the partially ionized plasma slabs have been studied extensively, for radio-frequency (rf) wave communication and control, material processing, and other applications. [3][4][5][6][7][8][9][10] Especially, the interaction between partially ionized plasmas and electromagnetic (EM) waves becomes a key issue not only in the fundamental studies, but also in the practical applications. [11][12][13] Take communication and control during spacecraft reentry for example, as to the case with a highly nonuniform plasma layer covering the vehicle, understanding of the interaction between EM waves and such typical plasmas is crucial to performance reliable communication, and extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…9 In dielectric-bounded SWP sources, more than 200 W microwave power is injected. [1][2][3][4][5][6][7][8][9][10][11][12] In MVP sources, microwave plasmas are produced along a dielectric-free metal antenna and the surface waves propagate along the plasma-sheath interfaces. In 2005, Kousaka et al 13 at Nagoya University reported a new SWP source which can generate over-dense plasma along the surface of a negative biased metal rod, called metal-antenna surface wave excited plasma (MASWP).…”
Section: Introductionmentioning
confidence: 99%